An Exploratory Study of Woolworths Consumer's Post-Covid Food Waste Behaviour - Sartor, Dean (The IIE, 2021)
Food waste is a widespread global issue that negatively impacts people, economies, the environment and society (Liljestrand, 2017). In order for modern brands to remain relevant, they are expected to become more responsible, so as to be seen as meaningful and as brands with purpose (Wieland, 2017). These brands need to be committed to the integration of the needs of their stakeholders, their well-being, sustainability and the creation of shared value (Cook, Erwin, Carmody & Enslin, 2010). Thus, using an interpretivist paradigm which took a qualitative, phenomenological approach, the study aimed to explore post-covid food waste behaviours from the perspective of eight Woolworths consumers based in Johannesburg, South Africa. A thematic analysis was used to identify four primary themes, namely, consumer brand preference, post-covid food waste behaviours, Woolworth’s food waste strategies and Woolworth’s brand impact and purpose. The findings of the study indicated that although food waste was viewed as negative and irresponsible, many of Woolworths’ consumers believed that Covid-19 resulted in a dramatic increase, with the sweeping behavioural changes on both a consumer and retailer level being identified as the cause. Furthermore, most consumers felt that Woolworths helped to minimise food waste both at home and in-store through a variety of strategies and initiatives, as outlined in the waste hierarchy framework. These findings suggested that Woolworths is seen as a positive, meaningful and purposeful brand which stands for more than just profit, especially within a post-covid context. Moreover, the findings suggested that Woolworths should focus on educating consumers on the brand’s contributions to local communities and how Woolworths works to reduce food waste through their various strategies and initiatives. Additionally, the findings implied there is a lack of knowledge surrounding the topic and indicates that it is important for further large-scale and culturally-specific research to be conducted in order to gain an in-depth understanding of the topic, to raise consumer awareness and to uncover the best ways to avoid food waste.
Keywords: Responsible brands; Meaningful brands; Brand purpose; Sustainability; Shared Value Creation; Consumer brand preference; Waste Hierarchy Framework; Consumer education